Burnout and Its Antecedents: Considering Both Work and Household Time Claims, and Flexibility in Relation to Burnout - Li, Shuanglong; ten Berge, Jannes; Kristiansen, Marcus H. (Frontiers in Public Health, 2022)
This study contributes to the previous literature by examining how flexible work arrangements interact with work and family time claims to affect burnout. It does so by providing a theoretical framework and empirical test of the interaction of flexibility with the effect of work and family time claims on burnout. Hypotheses and predictions based on previous literature are tested by Ordinary Least Squared regression models using data from the Time Competition Survey, constituting a sample of 1058 employees of 89 function groups within 30 organizations. We found no main effects of work and family time claims or flexible work arrangements on burnout. However, the results do show an interaction of flexible working hours with the effect of work and family time claims on burnout. Specifically, the higher an individual's work and family time claims, the more this person benefits from having flexible working hours. All in all, the results support the proposition that the relationship between work and family time claims and burnout differs for individuals with different levels of flexible work arrangements.